The Role of Commercial Diplomacy in Promoting India as a Destination for Higher Education: A Case Study of Sudan - B. S. Mubarak; Manish Sinha (Australasian Accounting, Business and Finance Journal, 2023)
There are several studies on the internationalization of higher Education in India. However, most of these studies are based on initiatives that have been taken up by private universities in India. Indian Embassies and Consulates (Indian Missions) around the world play an important role in promoting India as a destination for higher education among foreign students. Indian Missions become the first interface for foreign students travelling to India. Sudan is the third largest African country, with a population of over 45 million. India is one of the preferred destinations for Sudanese students travelling abroad for higher studies. Annually about 1500 students travel to India for higher studies, mainly to Pune, Mumbai, Hyderabad, Chennai and Bangalore. A study was conducted on students who have completed University education in India to understand the role of Commercial Diplomacy and Indian Missions in promoting India as a destination for higher education. The outcome of the study provides insights into the importance of Commercial Diplomacy and the role of Indian Missions in promoting India as a destination for Higher Education. Outreach events to promote India as a destination for Higher Education and facilitation of Student visas play a major role in students choosing India as a destination for higher education.
Keywords: Commercial Diplomacy; Internationalization of education; Indian Missions abroad